Ethical AI in Social Media: Preventing Harmful Content and Misinformation (Journal of responsible AI & ethics, 2026)
Artificial Intelligence has become an essential component of modern social media platforms, shaping how information is generated, moderated, and distributed among billions of users worldwide. While AI-driven systems enable rapid content moderation and recommendation, they also present ethical challenges related to misinformation, harmful content, bias, and manipulation. The increasing reliance on algorithmic systems has raised concerns regarding transparency, accountability, fairness, and the protection of public discourse. This paper explores the ethical role of Artificial Intelligence in social media environments, focusing on mechanisms for preventing harmful content and misinformation while preserving freedom of expression and democratic participation. The study investigates how AI moderation systems detect and manage misleading information, hate speech, propaganda, and harmful digital behaviors. It examines ethical frameworks, regulatory policies, and technological tools designed to improve algorithmic responsibility in social media platforms. Through empirical observations, case studies, and analytical evaluation of AI-based moderation systems, the research identifies strengths and weaknesses in current approaches to content moderation.